Cultural politics and cultural needs in the programs of the political parties in Bosnia and Herzegovina (Republic Srpska and the Federation of Bosnia and Herzegovina) - Ćorluka, Bojan J (Napredak, 2022)
Every society is interested in getting to know and accepting the rules of behaviour and all other elements of culture through which individuals integrate themselves into the society and identify with it. Culture is a cohesive element of society that connects individuals, social groups and all other social segments into a single unit. In the first part of the paper, the concept of culture is defined, through the concepts of cultural politics and cultural needs. The second part of the paper presents the analysis results regarding the content of the programs and statutes of nine parties in Republic Srpska (RS) and the Federation of Bosnia and Herzegovina (FBiH), which won the greatest number of votes in the 2022 general election, from the cultural politics and cultural needs point of view. The research into the relations between political parties and cultural politics shows that this topic is being marginalized in programs and statutes of all political parties in Bosnia and Herzegovina (BiH).